2015
DOI: 10.1016/j.injury.2015.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Injury patterns of medial patellofemoral ligament and correlation analysis with articular cartilage lesions of the lateral femoral condyle after acute lateral patellar dislocation in adults: An MRI evaluation

Abstract: Firstly, the MPFL is most easily injured at the FEM, and secondly at the PAT in adults after acute LPD. The complete MPFL tear is more often concomitant with osteochondral lesions of the lateral femoral condyle than the partial MPFL tear. The isolated patellar-sided MPFL tear is more easily concomitant with chondral lesions and osteochondral lesions of the lateral femoral condyle than the isolated femoral-sided MPFL tear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 52 publications
5
51
0
2
Order By: Relevance
“…Specifically, the patella is affected in 11.0–37.5%, while the trochlea is involved in only 6.0–15.5% of the patients . Patellofemoral joint biomechanics have been considered having an important role in cartilage pathology . Indeed, the incidence of patellar chondral lesions with recurrent patellar dislocations is exceedingly high, ranging from 73.5% to 95.7% in MRI and arthroscopic studies .…”
Section: Incidence Of Chondral Defects On the Different Topographies mentioning
confidence: 99%
“…Specifically, the patella is affected in 11.0–37.5%, while the trochlea is involved in only 6.0–15.5% of the patients . Patellofemoral joint biomechanics have been considered having an important role in cartilage pathology . Indeed, the incidence of patellar chondral lesions with recurrent patellar dislocations is exceedingly high, ranging from 73.5% to 95.7% in MRI and arthroscopic studies .…”
Section: Incidence Of Chondral Defects On the Different Topographies mentioning
confidence: 99%
“…Key areas of injury include the medial patellofemoral ligament (MPFL), as well as cartilage and bone on the patella and/or trochlea [19,37,42]. Dysfunction of the knee can result from injury to these structures [39].…”
Section: Introductionmentioning
confidence: 99%
“…The literature reports chondral lesions on MRI in 13 to 44% of patients. [9][10][11][12][13] In a prospective MRI analysis of adults with an acute lateral patellar dislocation, Zhang et al found the MPFL to be injured in 98% (119/121) of patients. Partial or incomplete tears were found in 40% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Injury of the lateral femoral condyle was seen in 22.3% (27/121) with osteochondral and chondral lesions comprising 13.2% (16/121) and 9.1% (11/121), respectively. 13 If the dislocation is subacute, the edema within the MPFL and chondral injury will be absent, but predisposing factors for dislocation, such as trochlear dysplasia, patella alta, or increased tibial tubercle (TT)-trochlear groove (TG) or TT-posterior cruciate ligament distance can be seen.…”
Section: Discussionmentioning
confidence: 99%